Answer:
Step-by-step explanation:
3x-2y= 100
3x= 10 +2y
x =(10+2y)/
Answer:
x = 1
y= -2
Step-by-step explanation:
to solve this system of equation , simultaneously using the substitution method
we say let
7 x + y = 5 ............................................. equation 1
2x - y = 4 ................................................... equation 2
from equation 2
2x - y = 4 ................................................... equation 2
2x - 4 = y
y = 2x -4.......................................................... equation 3
put the value of the y = 2x -4 into equation 1
7 x + y = 5 ............................................. equation 1
7x + 2x - 4 = 5
9x-4 = 5
9x = 5 + 4
9x = 9
divide both sides by the coefficient of x which is 9
9x/9 = 9/9
x = 1
substitute the value of x = 1 into equation 3
y = 2x -4.......................................................... equation 3
y = 2(1) -4
y = 2 - 4
y = -2
to check if you are correct put the value of x and y into any of the equations and you will see that the left hand side will be equal to the right hand side.
2x - y = 4 ................................................... equation 2
2(1) -(-2) = 4
2 + 2 = 4
4=4................................... proved
Answer:
There were 20 picks total
Step-by-step explanation:
We can use a proportion to solve this problem. Put the orange picks on top and the total picks on bottom
3 orange 12 orange
-------------- = ---------------
5 total x total
Using cross products
3x = 5*12
3x= 60
Divide each side by 3
3x/3 = 60/3
x = 20
There were 20 picks total
This is completing the square:
(x^2+12x+36)+42-36
Answer: (x+6)^2 +6
Remember, there is a missing term which is crucial to solving this, and that is 0x.
Ima use synthetic division, because that's the quicker option here:
The zero of x+2 is -2...
-2 | 3 5 1 0 -5
-6 2 -6 12
_____________
3 -1 3 -6 7
(Sorry, I'm unsure how to fix the formatting, plus I'm new to this. The -6 and such on the second line should be below the 5 and following of the first line, and the 3 and such on the last line should be below the 3 and following on the first line, leaving a space between the 3 on the first and third line.)
So the answer is: A. 3x^3 - x^2 + 3x - 6 + 7/(x+2)